Modeling the weekly cycle of NOx and CO emissions and their impacts on O3 in the Los Angeles‐South Coast Air Basin during the CalNex 2010 field campaign. Issue 3 (12th February 2016) - Kim, S.‐W.; McDonald, B. C.; Baidar, S.; Brown, S. S.; Dube, B.; Ferrare, R. A.; Frost, G. J.; Harley, R. A.; Holloway, J. S.; Lee, H.‐J.; McKeen, S. A.; Neuman, J. A.; et al.
Abstract: We developed a new nitrogen oxide (NOx ) and carbon monoxide (CO) emission inventory for the Los Angeles‐South Coast Air Basin (SoCAB) expanding the Fuel‐based Inventory for motor‐Vehicle Emissions and applied it in regional chemical transport modeling focused on the California Nexus of Air Quality and Climate Change (CalNex) 2010 field campaign. The weekday NOx emission over the SoCAB in 2010 is 620 t d −1, while the weekend emission is 410 t d −1 . The NOx emission decrease on weekends is caused by reduced diesel truck activities. Weekday and weekend CO emissions over this region are similar: 2340 and 2180 t d −1, respectively. Previous studies reported large discrepancies between the airborne observations of NOx and CO mixing ratios and the model simulations for CalNex based on the available bottom‐up emission inventories. Utilizing the newly developed emission inventory in this study, the simulated NOx and CO mixing ratios agree with the observations from the airborne and the ground‐based in situ and remote sensing instruments during the field study. The simulations also reproduce the weekly cycles of these chemical species. Both the observations and the model simulations indicate that decreased NOx on weekends leads to enhanced photochemistry and increase of O3 and Ox (=O3  + NO2 ) in the basin. The emission inventory developed in this study can be extended to different years and other urban regions in the U.S. to study the long‐term trends in O3 and its precursors with regional chemical transport models. Key Points: A fuel‐based inventory for NOx and CO in the Los Angeles Basin was developed The inventory was evaluated with the CalNex in situ and remote sensing data A regional model using this inventory reproduced observed weekly cycle of emissions and chemistry